Can labor policies reduce precarization? The case of youth employment in Italy - Caravaggio, Nicola (Structural change and economic dynamics, 2025)
The so-called Dignity Decree (DD), which came into force in summer 2018, represents one of the most significant legislative interventions in employment protection within the Italian labor market. This study examines the role of DD in shaping the career paths of young workers (aged 15-29) who recently entered the labor market. Specifically, we focus on their probability of being employed one year or more after the reform’s implementation and their likelihood of securing an open-ended contract within the same time frames. The analysis relies on an exclusive database of Compulsory Communications data and employs a Propensity Score Matching estimation. The findings suggest a modest improvement in the persistence of the labor market, with the probability of remaining employed increasing by approximately 1.5% one year after DD implementation. The result is more evident for open-ended contracts, with the probability of being employed in a permanent position rising to almost 4.5% after one year and half. Additionally, the DD is associated with a slight reduction in the number of contract activations and an increase in working days, reaching an additional 11 days 1.5 years after the reform’s introduction. •The study examines how the Dignity Decree (DD) shaped youth employment paths.•The analysis relied on highly disaggregated labor market’s administrative data.•After one year the reform raised young workers’ job retention by about 1.5%.•After 1.5 years, the chance of holding a permanent job rose by nearly 4.5%.•The DD cut contract activations and added 11 working days over the same span.•The DD cut contract activations and added 11 working days over the same span.